A revision of the ammonite faunas of the typeCenomanian. 2. The families Binneyitidae, Desmoceratidae, Engonoceratidae, Placenticeratidae, Hoplitidae, Schloenbachiidae, Lyelliceratidae and Forbesiceratidae - Kennedy, W; Juignet, P (1984)
In this part of the revision of the ammonite faunas of the type Cenomanianwe deal with representatives of the genera Borissiakoceras, Austiniceras, Neolobites, Metengonoceras, Placenticeras, Hyphoplites, Schloenbachia, Stoliczkaia (Lamnayella), Stoliczkaia (Shumarinaia), Euhystrichoceras and Forbesiceras. © 1984 Academic Press Inc. (London) Limited.